EFFECTS OF LONG-TERM ADMINISTRATION OF COOKED BEANS (Vigna unguiculata) DIET ON LEARNING AND MEMORY IN MICE - Aduema, W. (International Journal of Food Sciences, 2016)
Purpose: The neurotransmitter, serotonin has neurobehavioural actions which include mood, memory, learning and sleep. Beans, the stable diet of Nigerians contains serotonin and its precursor, 5-Hydroxytryptophan in significant amounts. It was therefore the aim of this study to find out whether long term consumption of cooked beans (Vigna unguiculata) diet has effects on some neurobehavioural parameters notably; learning and memory, using Swiss white mice as experimental animals. Method: Thirty (30) CD1 mice were randomly assigned into three groups, viz; (10, control, 20 Test) weighing 15-30g were fed normal rodent chow, 50% cooked beans diet (w/w) respectively and serotonin precursor (5-HTP) diet (0.2mg/50g w/w) for thirty days. All the mice had access to clean drinking water ad libitum. Before the neurobehavioural parameters were assessed, the phytochemical analysis of the beans, LD50 of the beans (Vigna unguiculata) and that of the serotonin precursor (5-HTP) were determined. Serotonin concentration was measured in the beans using gas chromatography analysis. Learning and memory, was investigated alongside food and water intake and body weight change. Involvement of serotonin pathway was investigated using the set of mice administered serotonin precursor for comparison with the beans diet fed mice. Mice were tested in the Morris water maze for 8 days: 3 days of acquisition training, 3 days of reversal training, 1 day of single probe trial and 1 day for visible platform task. Results: Learning on days 1, 2 & 3 of acquisition training was improved in the cooked beans and serotonin precursor diet-fed mice when compared to control (p<0.001, respectively). The trend was similar during the reversal training, memory was improved in the beans and serotonin precursor diet-fed mice when compared to control (p<0.001). During the probe trial, the swim duration in the South-East quadrant was significantly higher for cooked beans and serotonin precursor group compared to control (p<0.05). However, during the visible platform task, the swim latencies for the cooked beans and serotonin precursor group was significantly lower compared to control. Our finding therefore suggests that long term consumption of beans diet enhances learning and memory. Conclusion and Recommendation: In conclusion, long term consumption of cooked beans diet enhances learning and memory. If this research can be extrapolated to humans, we recommend that the serotonergic potential of beans may be harnessed in the prevention, treatment and management of behaviour/ mental disorders as this could potentially open up a vista for improved mental health status in populations globally.